1983
DOI: 10.1016/0005-2728(83)90045-2
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics and mechanism of oxidation of reduced spinach ferredoxin by molecular oxygen and its reduced products

Abstract: Reduced spinach ferredoxin reacts with molecular oxygen in an autocatalytic reaction characterized by a hyperbolic dependence on oxygen concentration. The kinetics of the reaction indicate formation of a reduced ferredoxin-oxygen intermediate complex and production of superoxide anion which my also react with reduced ferredoxin. Hydrogen peroxide, which is formed from superoxide, in turn reoxidizes reduced ferredoxin at a rate nearly 10-times faster than that of the cmnperable reaction with oxygen. The kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Electron transport and ATP synthesis rates decline in parallel (Table I) The differences seen in the presence and absence of NADP+ may be explained by the differing redox conditions imposed upon cyclic flow by noncyclic electron transport. In the absence of NADP, ferredoxin is forced to reduce only 02, and because this reaction is quite slow (9), it must result in larger pools of reduced ferredoxin and PQ. The addition of low concentrations of DCMU will cause a partial oxidation of both pools.…”
Section: Methodsmentioning
confidence: 99%
“…Electron transport and ATP synthesis rates decline in parallel (Table I) The differences seen in the presence and absence of NADP+ may be explained by the differing redox conditions imposed upon cyclic flow by noncyclic electron transport. In the absence of NADP, ferredoxin is forced to reduce only 02, and because this reaction is quite slow (9), it must result in larger pools of reduced ferredoxin and PQ. The addition of low concentrations of DCMU will cause a partial oxidation of both pools.…”
Section: Methodsmentioning
confidence: 99%
“…Takagi et al (2016) demonstrated that the ROS production site rather than the quantity of ROS is crucial for PSI photoinhibition. Reduced ferredoxin does not play a role in O 2 $ 2 generation at PSI, since the reaction of reduced ferredoxin with oxygen is rather slow (Hosein and Palmer, 1983).…”
Section: Advancesmentioning
confidence: 99%
“…In chloroplasts, the Fe atoms of Fd seem to fulfill the role of metal catalysts (Elstner and Konze, 1974;. The hydroxyl radical can also be formed from hydrogen peroxide and reduced Fd (Hosein and Palmer, 1983;Bowyer and Camilleri, 1985). The hydroxyl radical can initiate self-propagating peroxidative reactions leading to the destruction of membrane lipids and of DNA, and hence to extensive tissue damage (see Bowler et al, 1992, for review).…”
mentioning
confidence: 99%